A gene expression signature for RSV: clinical implications and limitations. - Peter J M Openshaw (PLoS Medicine)
Peter Openshaw discusses the challenges in advancing respiratory syncytial virus (RSV) treatments and the implications of a study by Mejias and colleagues using a newly identified gene signature for diagnosis and prediction of RSV severity. Please see later in the article for the Editors' Summary.